2017
DOI: 10.1093/infdis/jix071
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Against the Staphylococcus aureus Bicomponent Leukotoxin AB Isolated Following Invasive Human Infection Reveal Diverse Binding and Modes of Action

Abstract: The 2-component leukotoxin LukAB is critical for Staphylococcus aureus targeting and killing of human neutrophils ex vivo and is produced in the setting of human infection. We report 3 LukAB-specific human monoclonal antibodies (mAbs) with distinct mechanisms of toxin neutralization and in vivo efficacy. Three hybridomas secreting mAbs with anti-LukAB activity (designated SA-13, -15, and -17) were generated from B cells obtained from a 12-year-old boy with S. aureus osteomyelitis. Each of the 3 mAbs neutralize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…Owing to leukocidin structural dissimilarities, this mAb does not neutralize LukAB 103 . However, the identification of a series of mAbs that specifically neutralize LukAB was recently described 22 , this included naturally occurring mAbs isolated from infected chlidrens 105 . The role of LukAB in the intracellular compartment, where it promotes bacterial escape after phagocytosis 37,63 , is likely to pose challenges for neutralization of this toxin.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Owing to leukocidin structural dissimilarities, this mAb does not neutralize LukAB 103 . However, the identification of a series of mAbs that specifically neutralize LukAB was recently described 22 , this included naturally occurring mAbs isolated from infected chlidrens 105 . The role of LukAB in the intracellular compartment, where it promotes bacterial escape after phagocytosis 37,63 , is likely to pose challenges for neutralization of this toxin.…”
Section: Therapeuticsmentioning
confidence: 99%
“…To date, all antibody-based therapeutics against S. aureus have failed to show significant efficacy in clinical trials (9). Results of preclinical studies of leukocidin-specific monoclonal antibodies are promising, and important issues such as breadth of neutralization and potency in vivo warrant further investigation (20,21). Passive immunization with an "antibody cocktail" against multiple different S. aureus virulence factors will likely be needed for a successful antibodybased therapeutic (9,22).…”
Section: Figmentioning
confidence: 99%
“…Our study results provide insight into direct toxin neutralization by naturally occurring antibodies pooled in IVIg. Previous data from our group have shown that functional antitoxin antibody responses following invasive human infection are diverse and that toxin neutralization can be achieved by interfering with multiple steps in the cytolysis pathway (20).…”
Section: Figmentioning
confidence: 99%
“…Therefore, targeting alternate antigens on the S . aureus cell surface as well as toxins, and the identification of novel immunotherapeutics are still being explored with priority [ 11 21 ]. One of the key virulence factors on the surface of S .…”
Section: Introductionmentioning
confidence: 99%